DIGITAL HEALTH GOVERNANCE WITHIN THE ARCHITECTURE OF STUNTING PREVALENCE MITIGATION: A CONVERGENCE OF DATA INTEGRATION, TECHNOLOGICAL INNOVATION, AND PUBLIC POLICY DYNAMICS (Lex localis - Journal of Local Self-Government, 2025)
This study aims to explore in depth the architecture of Digital Health Governance in constructing an integrated, ethical, and evidence-based framework for stunting mitigation in West Nusa Tenggara Province (NTB), Indonesia. Employing a qualitative-descriptive approach with a case study design, the research focuses on the dynamic interrelations between digital technology, health bureaucracy, and beneficiary communities. Data was collected through in-depth interviews, participatory observations, and analysis of policy documents and digital systems (including SIGIZI, e-PPGBM, SIGA, and the NTB Stunting Dashboard), and subsequently analyzed using thematic and source triangulation techniques. The findings reveal that cross-sectoral data fragmentation, digital literacy disparities, and weak ethical data regulations constitute major structural barriers to the implementation of digital health governance. Nonetheless, significant opportunities arise from the strengthening of data interoperability and pentahelix collaboration, enabling early detection and rapid response to stunting risks. The study concludes that socio-technological resilience and digital equity are the pivotal determinants for successful stunting mitigation in the digital transformation era. The research recommends the establishment of a federated data system-based Digital Health Governance ecosystem that ensures data sovereignty, policy transparency, and sustained community participation.